To be a writer is a paradox (Palíndromo, 2016)
The texts “Writing”  of  Margueri- te Duras and the thesis “Marcel Brood- thaers: Museum of Modern Art, Depart- ment of Eagles, now in Portuguese” by Keila Kern are covered on this essay as a fiction, on one hand and on the other, as an analysis of the Museum of Modern Art and its possible points of contact with the writing process of Marguerite Duras and Keila Kern’s curatorial process.
Keywords: museum; contemporary art; Marcel Boodthaers; literature; Marguerite Duras